The psychological state on the post injured football athletes / Muhammad Afif Asmadi - Asmadi, Muhammad Afif (Faculty of Sport Sciences and Recreation, 2020)
The purpose of this study was to identify the psychological state on the post-injured football players. About 124 players from Kuantan Football League were selected as the subject through purposive sampling technique and were divided into two groups which was post-injured players and non-injured players. This two groups were then to answer Depression Anxiety and Stress Scale (DASS-21) questionnaire to measure the stress, anxiety and depression level of these two groups. Scores of the data were then analyzed through the use of Graphpad Prism using an independent sample t-test as the statistical analysis. The results of the study had found that there was a significant difference between two groups for their stress, anxiety and depression levels. Hence, it can be concluded that the psychological state of the post-injured players will be affected due to the injury and can be used as the benchmark to monitor their psychological responses.